Novel insertion/deletion polymorphisms and genetic features of the shadow of prion protein gene (SPRN) in dogs, a prion-resistant animal - Kim, Yong-Chan; Kim, Hyeon-Ho; Kim, An-Dang; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2022)
Prion diseases are fatal infectious neurodegenerative disorders that are induced by misfolded prion protein (PrPSc). Previous studies have reported that the shadow of prion protein (Sho) encoded by the shadow of prion protein gene (SPRN) plays a critical role in stimulating the conversion process of normal PrP (PrPC) into PrPSc, and genetic polymorphisms of the SPRN gene are significantly related to susceptibility to prion diseases. Recent studies have reported that dogs show prion resistance, and there have been several attempts to identify resistance factors to prion diseases in dogs. However, there has been no study of the canine SPRN gene thus far. We investigated genetic polymorphisms of the canine SPRN gene in 201 dogs using amplicon sequencing and compared the number of SPRN polymorphisms among prion-related species. In addition, we performed multiple sequence alignments of the amino acid sequences of Sho among prion-related species by ClustalW and analyzed the 3D structure of Sho using AlphaFold. Furthermore, we assessed the protein–protein interaction of canine PrP with canine Sho carrying wild-type and mutant alleles using HawkDock. We found 4 novel insertion/deletion polymorphisms of the SPRN gene in 201 dogs and identified a significant difference in the number of SPRN polymorphisms between prion-susceptible and prion-resistant animals. In addition, Sho has two α-helixes linked with the coil. Furthermore, we found different binding complexes and binding free energies between canine Sho and PrP according to SPRN polymorphisms. To the best of our knowledge, this is the first report of canine SPRN polymorphisms.